Evaluation of the ethanolic extract of Myconia albicas (Old Cinnamon) in the alternative model of anxiety in zebrafish (Research, Society and Development, 2022)
Myconia albicans is the most abundant genus of the melastomaceous botanical family. In Brazil, it is known as "Canela de Velho", and is used mainly in inflammatory processes. Due to the scarcity of scientific works that report its pharmacological effect, the objective of this study was to perform its chemical characterization, toxicity, and the possible effect on the nervous system, using the experimental model Zebrafish (Dario regio). The organic extract of ethyl acetate (EtOAc) was elaborated through the dry leaves of the cinnamon tree of old. The EtOAc sample was submitted to preliminary phytochemical screening and showed the presence of phenols, flavanoids of the flavones type, flavonols and xanthones, triterpenoids, and alkaloids. Then, flavonoid compounds (369.58±0.074mgEQ/g) and total phenols (81.48±0.005mgEAG/g) were determined. EtOAc was evaluated for its toxicity, with Artemia salina, which showed low toxicity in all the studied doses. In the pharmacological action tests, the doses of 3, 10, or 30 mg/mL were used; 20 µL; oral (v.o.) or intraperitoneal (i.p.). The locomotor activity was evaluated in the open field test, which showed a decrease in the fish.  And the anxiolytic activity, in the light & dark preference test, showed that EtOAc at 30 mg/mL, when administered intraperitoneally (IP), has an anxiolytic effect similar to Diazepam IP control. Thus the EtOAC of M. albicans showed the presence of total phenols and several flavonoids, with low toxicity, in which the highest dose presented anxiolytic effect in Zebrafish.